Pengaruh Pemberian Air Seduhan Serbuk Simplisia Seledri (Apium Graveolens) Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi. - Haryati Haryati; Yuyun; Vivi Kurniati Tjahjadi; Adi Suhardi Herjanto (Sekolah Tinggi Agama Buddha Nalanda, 2021)
Hypertension is a major risk factor for cardiovascular disease which is a major cause of death worldwide. The purpose of thisstudy was to determine the effect of water administration of celery powder (Apium graveolens) on blood pressure reductionin hypertensive patients. Celery (Apium graveolens) contains Apigenin which can prevent narrowing of the arteries(vasodilation) and Pthalides which can relax the artery muscles or relax blood vessels (vasorelaxation). This research usesfield observation method with a case study approach. Pre-treatment and post-treatment design. The results of the study of casestudies 1, 2, 3 and 4 showed an average result of a decrease in systolic pressure of 57.5 mmHg and diastolic of 25 mmHg.Study 5 as a control obtained results in lower blood pressure reduction. The conclusion of this study is the provision of watersteeping powder of celery simplicia influences in the form of decreased blood pressure and improved quality of life of patientswith hypertension.